Tingkat Pengetahuan dan Motivasi Petani Padi Sawah Tentang Asuransi Usahatani Padi (AUTP) Di Kota Kendari - Fayadh Mahdi Halida; Surni Surni; Lukman Yunus (Universitas Halu Oleo, 2021)
The purpose of this study is to analyze the level of farmers' knowledge about the mechanism for implementing Rice Farming Insurance; analyzing the motivation of lowland rice farmers in participating in Rice Farming Insurance; analyze the relationship between farmers' knowledge and motivation in participating in Rice Farming Insurance. The population in this study were 190 lowland rice farmers in Kendari City who participated in the Rice Farming Insurance program. Sampling was done by census. The research variables consisted of: farmers' knowledge and motivation to participate in Rice Farming Insurance. The level of farmers' knowledge was analyzed descriptively based on the revision of the Bloom Taxonomy in the cognitive domain, while to analyze the relationship between knowledge and motivation of farmers in participating in Rice Farming Insurance, the Spearman Rank correlation test was used. The results of the study show that lowland rice farmers in Kendari City have low knowledge of the mechanism for implementing Rice Farming Insurance; the motivation of farmers in participating in Rice Farming Insurance is in the high category. The result of the Spearman Rank correlation test shows that between knowledge and motivation of farmers in joining Rice Farming Insurance has a strong and significant level of relationship.Keywords: knowledge; motivation; Rice Farming Insurance